REGRESION MODEL OF COVID-19 MEDICAL HARZARDOUS WASTE GENERATION BASED ON MAXIMUM BEDS CAPACITY OF REGIONAL HOSPITALS IN DKI JAKARTA - Mr Prihartanto (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2020)
The Covid-19 pandemic disaster in DKI Jakarta has shown a significant increasing in confirmed positive cases starting in September 2020, resulting in the re-implementing of Large-Scale Social Distancing (PSBB). The main factor that led to the re-implementing of the PSBB in DKI Jakarta is the limited bed capacity in the 67 Covid-19 referal Local General Hospitals (RSUD). Handling Covid-19 patients requires more medical equipment such as masks, glasses, protective clothing and so on, which will increase the rate of medical waste generation. This study will discuss the prediction of minimum and maximum generation of Covid-19 medical hazardous waste (B3) in 67 Covid-19 referal RSUD in DKI Jakarta which can be calculated based on the maximum capacity of available isolation and ICU beds during the period 23 August - 4 October 2020 and the average of medical waste generation per patient treated. From the prediction, a regression model of increasing number of minimum and maximum medical hazardous waste produced in several Covid-19 referal RSUD in DKI Jakarta can be made. Keywords: covid-19, hazardous waste, hospital, maximum capacity, regression model.